Mapping the Global Landscape of Electronic Supply Chain Management (e-SCM): A Bibliometric and Visual Analysis - Aditya Lapu Kalua; Mochamad Agung Wibowo; Luther Alexander Latumakulita (Asosiasi Doktor Sistem Informasi Indonesia, 2026)
This study maps the intellectual structure of global electronic supply chain management (e-SCM) research through a bibliometric analysis of Scopus-indexed publications published between 2015 and 2025. The retrieval workflow began with the Scopus query TITLE-ABS-KEY (